2017
DOI: 10.21873/anticanres.12138
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the miRNA Profiles of Melanoma Exosomes Derived Under Normoxic and Hypoxic Culture Conditions

Abstract: The miRNA-expression profiles of exosomes from patient-derived melanoma cells are modified by oxygen concentration and reflect the phenotypic changes of melanoma cells under different growth conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 45 publications
2
25
0
Order By: Relevance
“…Our findings about the molecular cargo of sEVs are in accordance with previous studies, which also showed changes in the exosomal content upon exposure of the donor cells to external stimuli and stress conditions 41,44,47,48 . Furthermore, Peinado et al 17 and Lazar et al 49 , analysing protein composition of different melanoma cell line-derived exosomes, also found melanocyte-specific proteins, transmembrane proteins, such as tetraspanins, transporters and receptors as well as MVB and endosomal pathway-related proteins, for instance ESCRT-associated proteins, annexins, cytoskeletal and small GTP-binding proteins 17,49 . comprehensive in silico analysis of functional differences between sEV groups.…”
Section: Encapsulation Of Ag-tio 2 Nanoparticles Into Sevs Cannot Be supporting
confidence: 92%
See 1 more Smart Citation
“…Our findings about the molecular cargo of sEVs are in accordance with previous studies, which also showed changes in the exosomal content upon exposure of the donor cells to external stimuli and stress conditions 41,44,47,48 . Furthermore, Peinado et al 17 and Lazar et al 49 , analysing protein composition of different melanoma cell line-derived exosomes, also found melanocyte-specific proteins, transmembrane proteins, such as tetraspanins, transporters and receptors as well as MVB and endosomal pathway-related proteins, for instance ESCRT-associated proteins, annexins, cytoskeletal and small GTP-binding proteins 17,49 . comprehensive in silico analysis of functional differences between sEV groups.…”
Section: Encapsulation Of Ag-tio 2 Nanoparticles Into Sevs Cannot Be supporting
confidence: 92%
“…These areas have a special chemical microenvironment with low oxygen, low pH and low nutrient concentration. Intrinsic stress conditions, such as hypoxia and acidosis increase exosome release from malignant cells and lead to TME alteration and expansion, which subsequently results in tumour progression 48,49 .…”
Section: Role Of Intrinsic Microenvironmental Factors In the Exosome-mentioning
confidence: 99%
“…Micro RNA profiles of TEX differ from miRNA profiles of their donor cancer cells as well as from profiles of sEV released by normal cells [ 78 , 79 , 80 , 81 ]. The majority of available works report miRNA signatures of pure MTEX released in vitro by melanoma cell lines [ 69 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ]. Moreover, a few studies addressed miRNA composition of sEV derived from serum/plasma of melanoma patients [ 82 , 91 , 92 , 93 , 94 ].…”
Section: The Molecular Cargo Of Mtexmentioning
confidence: 99%
“…Similar to proteomics data, few consistencies were observed among these studies due to different models applied. Nevertheless, there were 6 MTEX-upregulated miRNA species reported in more than one study: miR-494 [ 82 , 83 ], let-7c [ 69 , 84 ], miR-690 [ 84 , 85 ], miR-17 [ 84 , 91 ], and miR-494 [ 82 , 83 ], while miR-125b was reported to be downregulated in MTEX or sEV from plasma of melanoma patients [ 83 , 92 ]. Noteworthy, all the above mentioned miRs are known to be involved in cancer cell invasion, migration, and proliferation as well as in inflammatory processes linked to tumorigenesis and cancer progression [ 82 , 83 , 84 , 85 , 86 , 91 , 92 ].…”
Section: The Molecular Cargo Of Mtexmentioning
confidence: 99%
“…Hypoxic conditions promote the invasive potential of malignant melanocytes [ 92 ] and increase the amount of specific miRNAs in exosomes (e.g., miR-494, miR-513a, miR-4497, miR-6087) [ 93 , 94 ]. Hypoxia-inducible factor 1 alpha (HIF1α), key player in the cellular response to oxygen deprivation [ 95 ], promotes the expression of several miRNAs (miR-210, miR-218, miR-224, and miR-452) that contribute to tumour cell plasticity and aggressiveness, by targeting and increasing BNIP3 (BCL2/adenovirus E1B interacting protein 3), associated with glutamine metabolism [ 96 , 97 , 98 ].…”
Section: Non-coding Rnas and The Interplay With The Melanoma Micromentioning
confidence: 99%